A Higher Fructose Intake Is Associated with Greater Albuminuria in Subjects with Type 2 Diabetes Mellitus. (17th October 2018) - Gómez-Sámano, Miguel Ángel; Almeda-Valdes, Paloma; Cuevas-Ramos, Daniel; Navarro-Flores, María Fernanda; Espinosa-Salazar, Héctor Donaldo; Martínez-Saavedra, Mayela; León-Domínguez, Jefsi Argelia; Enríquez-Estrada, Víctor Manuel; López-González, Ana Laura; Sarmiento-Moreno, Ana Laura; Rivera-González, Lucero Alejandra; Juárez-León, Óscar Alfredo; et al.
Abstract : The aim of this single center cross-sectional study was to investigate the association between fructose intake and albuminuria in subjects with type 2 diabetes mellitus (T2DM). This is a single center cross-sectional study. One hundred and forty-three subjects with T2DM were recruited from the Instituto Nacional de Ciencias Medicas y Nutricion Salvador Zubiran. The median daily fructose intake was estimated with a prospective food registry during 3 days (2 week-days and one weekend day) and they were divided into low fructose intake (<25 g/day) and high fructose intake (≥ 25 g/day). Complete clinical and biochemical evaluations were performed, including anthropometric variables and a 24-hour urine collection for albuminuria determination. One hundred and thirty-six subjects were analyzed in this study. We found a positive significant association between daily fructose intake and albuminuria (ρ = 0.178, p=0.038) in subjects with type 2 diabetes mellitus. Other variables significantly associated with albuminuria were body mass index (BMI) (ρ = 0.170, p=0.048), mean arterial pressure (MAP) (ρ = 0.280, p=0.001), glycated hemoglobin (A1c) (ρ = 0.197, p=0.022), and triglycerides (ρ = 0.219, p=0.010). After adjustment for confounding variables we found a significant and independent association between fructose intake and albuminuria (β = 13.96, p=0.006). We found a statistically significant higher albuminuria (60.8 [12.8-228.5] versus 232.2 [27.2-1273.0] mg/day, p 0.002), glycated hemoglobin (8.6±1.61 versus 9.6±2.1 %), p= 0.003, and uric acid (6.27±1.8 versus 7.2±1.5 mg/dL), p=0.012, in the group of high fructose intake versus the group with low fructose intake, and a statistically significant lower creatinine clearance (76.5±30.98 mL/min versus 94.9±36.8, p=0.014) in the group with high fructose intake versus the group with low fructose intake. In summary we found that a higher fructose intake is associated with greater albuminuria in subjects with T2DM.